Long Non-coding RNA MALAT1 Alleviates the Elevated Intraocular Pressure (Eiop)-induced Glaucoma Progression via Sponging miR-149-5p. (3rd June 2021) - Wang, Linling; Gong, Jin; Wang, Junling; Dan, Jing; Wang, Ping
ABSTRACT: Background : Glaucoma is an optic neuropathic disease and contributed to the irreversible blindness caused by the slow death of retinal ganglion cells (RGCs). Long non-coding RNA (lncRNA) metastasis associated lung adenocarcinoma transcript 1 (MALAT1) was reported to be aberrantly expressed in diverse diseases, including glaucoma. However, the mechanism of MALAT1 in glaucoma was still undefined. Methods : The levels of MALAT1, microRNA-149-5p (miR-149-5p) in RGCs cultured under elevated pressure were measured by quantitative real-time polymerase chain reaction (qRT-PCR). The putative target of MALAT1 was predicted by starBase v2.0 online database, and dual luciferase reporter assay, RNA immunoprecipitation (RIP) assay and RNA pull-down assay were performed to verify this interaction. The cell viability of RGCs was measured by Cell Counting Kit-8 (CCK-8) assay. The apoptotic rate was evaluated via flow cytometry. The protein levels of apoptosis-related proteins (Bax, B-cell lymphoma 2 (Bcl-2)) and Cleaved caspase 3 were assessed by Western blot. Results : The level of MALAT1 was significantly down-regulated, and the level of miR-149-5p was distinctly up-regulated in RGCs under pressure in a dose-dependent manner. Functionally, MALAT1 overexpression or miR-149-5p inhibitor alleviated the inhibitory effect on cell viability and the promoted effect on apoptotic rate of RGCs in EIOP. The interaction between MALAT1 and miR-149-5p was predicted by starBase v2.0 online database, and dual luciferase reporter assay, RIP assay and RNA pull-down assay validated the interaction. Combined with the loss and gain experiment results, miR-149-5p was negatively interacted with MALAT1. Furthermore, miR-149-5p mimics mitigated the promoted impact on cell viability and the suppressive impact on apoptotic rate by targeting MALAT1. Conclusion : MALAT1 promoted cell proliferation and inhibited cell apoptosis of RGCs via targeting miR-149-5p in glaucoma in vitro, which might shed light on the mechanism of glaucoma pathogenesis.